T-CD4+ DAN PROFIL LIPID DI HIV (T-CD4+ and Lipid Profile in HIV) - Yulia Hayatul Aini; Coriejati Rita; Agnes Rengga Indrati; Rudi Wisaksana (Indonesian Association of Clinical Pathologist and Medical laboratory, 2014)
Human Immunodeficiency Virus (HIV) infection patients are often reported to be associated with changes of lipid metabolism.A previous study suspected that there was a correlation between low CD4+ T-lymphocyte counts with the lipid profile in HIV-infectedpatients. The objective of this study was to know the assessment of the lipid profile (total cholesterol, HDL, LDL and triglyceride) inpatients with HIV infection and their correlation with CD4+ T-Lymphocyte count. This study was conducted at the Hasan Sadikin Hospital,Bandung using retrospective data, and analysis method as the study design. The study was performed on 402 HIV-infected patients.A significant difference was found in all lipid parameters between patients with and without ART (p<0.05). Weak correlations werefound between CD4+ T-Lymphocyte with total cholesterol and HDL levels (r<0.04), and a very weak correlation as well with the LDLlevel (r<0.2). There was no correlation with the triglyceride levels (p=0.751). The lipid profile showed a weak correlation with CD4+T-Lymphocyte, therefore, it can not be used as a parameter to know the severity of disease relating to the HIV infection. However, it canbe useful for monitoring the metabolic effect of the given therapy, because there was a significant difference between those patients withand without ART.